Production of Maranta arundinacea and Myrosma cannifolia in agroforestry system - Castro, Cristina Maria; Devide, Antonio Carlos Pries (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Food culture, the use and protection of biodiversity should be encouraged with a view to food security, sovereignty and health. Arrowroot is part of our cultural heritage, having been cultivated and consumed by pre-Columbian populations. In the Atlantic Forest biome, arrowroot grows in understory, produces rhizomes rich in highly digestible and gluten-free starch, used as a fortifier by our ancestors. The objective of this research was to compare the productive performance of common arrowroot (Maranta arundinacea) and ‘guapo’ (Myrosma cannifolia) in an agroforestry management with Gliricidia sepium and banana shrub Nanicão, during five production cycles. The production of M. arundinacea (19.8 t/ha) surpassed M. cannifolia (8.5 t/ha). Rainfall and height of G. sepium were the components that best explained the drop in rhizome production of M. cannifolia as the most drought-sensitive species. The inclusion of G. sepium in the agroforestry system is of importance due to the high contribution of organic residues added to the soil.